Pelatihan Perhitungan Harga Pokok Penjualan Kain Tenun pada Usaha Mikro Kecil Menengah di Kecamatan Cawas Kabupaten Klaten - Desi Astika R; Rochmad Bayu Utomo (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
In the continuity of the business being run, it is important to know the profit obtained for each product, which is calculated on the cost of goods sold. However, this weaving entrepreneur in Pakisan Village does not calculate the cost of goods sold while running his business. They choose to focus on production and product sales because they don't want to make it difficult to think about recording related to production expenses. They consider calculating the cost of goods sold to be difficult because they cannot understand and practice calculating the cost of goods sold. Therefore, the service wants to share knowledge by conducting training in calculating the cost of goods sold for its woven fabrics. The aim of this community service is to provide knowledge and understanding to weaving entrepreneurs regarding calculating the cost of goods sold. The methods that will be used in this service are the interview, socialization, training and evaluation stages. After the service provided an explanation regarding the cost of goods sold, the weaving business owner better understood the benefits of the cost of goods sold and was willing to carry out training in calculating it.